Combined Locked Nucleic Acid Probes and High-Resolution Melting Curve Analysis for Detection of Rifampicin-Resistant Tuberculosis in Northern Thailand - Thant Y.M. (2023)
Rifampicin-resistant tuberculosis (RR-TB) has become a major threat globally. This study aims to develop a new assay, RIF-RDp, to enhance the detection of RR-TB based on combined locked nucleic acid (LNA) probes with high-resolution melting curve analysis (HRM). Two new LNA probes were designed to target the class-III and IV mutations of rpoB, H526D, and D516V. LNA probes showed 100% specificity in the detection of mutant targets among characterized and blinded Mycobacterium tuberculosis (Mtb) isolates. The performance of RIF-RDp was evaluated using 110 blinded clinical Mtb isolates in northern Thailand against drug-susceptibility testing (DST), DNA sequencing, and a commercial real-time PCR kit. This assay showed sensitivity and specificity of 94.55% and 98.18% compared to DST, and 96.36% and 100% compared to DNA sequencing. The efficacy of RIF-RDp was comparable to the commercial kit and DNA sequencing. The Cohen’s Kappa statistic showed almost perfect agreement between RIF-RDp and the commercial kit (κ = 0.95), and RIF-RDp and DNA sequencing (κ = 0.96). Furthermore, this is the first report of the rare mutation profiles, S531W, and a triple codon deletion (510–512) in northern Thailand. According to high accuracy, the RIF-RDp assay may render an easy-to-use, low-cost, and promising diagnostics of RR-TB in the future.